Influence of Polybag Size and Interval of Liquid Organic Fertilizer of Banana Stones on The Growth and Results of Chilli Variety - Daryanti; Tyas Soemarah Kurnia Dewi; Achmad Fatchul Aziez; Endang Suprapti; Sapto Priyadi; Handayu Anis Fatmala (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2022)
Indonesian people will feel bland if they eat without chilli, the raw material is chilli, so people still consume chilli even though the price is expensive. This study aims to determine the effect of polybag size and interval of application of liquid organic fertilizer on banana stems on the growth and yield of Dewata's cayenne pepper that is cultivated organically in polybags. This study used a Completely Randomized Block Design (RAKL) with two treatment factors. The results showed that polybag size had a very significant effect on the parameters of plant height, the weight of fresh stover, the weight of dry stover, number of red fruit, number of green fruit and weight of green fruit, and did not significantly affect parameters of number of flowers and weight of red fruit. The interval of POC administration of banana stems had a very significant effect on the parameters of plant height, the weight of fresh stover, the weight of dry stover, number of flowers, number of red fruit, the weight of red fruit, number of green fruit and weight of green fruit. There was no interaction between polybag size and interval of administration of POC banana stems on growth and yield of cayenne pepper (Capsicum frutescens. L) Dewata variety.